2012
DOI: 10.1002/srin.201100186
|View full text |Cite
|
Sign up to set email alerts
|

Carbothermal Reduction of Iron Ore Applying Microwave Energy

Abstract: This paper presents the results of a study on carbothermal reduction of iron ore made under the microwave field in equipment specially developed for this purpose. The equipment allows the control of radiated and reflected microwave power, and therefore measures the microwave energy actually applied to the load in the reduction process. It also allows performing energy balances and determining the reaction rate with high levels of confidence by simultaneously measuring temperature and mass of the material upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…82 A recent study also suggested that the reduction reaction between iron ore and petroleum coke was highly dependent on microwave heating characteristics of the materials, whose effects could be evaluated by simultaneously measuring temperature and mass of materials during reduction. 83 Figure 10 shows a schematic of the microwave heating system for iron ore reduction in argon, in which two directional couplers were used. By using the couplers ('1' and '2' in Fig.…”
Section: Reduction Of Iron Oxides/ores Laboratory-scale Experimental ...mentioning
confidence: 99%
See 2 more Smart Citations
“…82 A recent study also suggested that the reduction reaction between iron ore and petroleum coke was highly dependent on microwave heating characteristics of the materials, whose effects could be evaluated by simultaneously measuring temperature and mass of materials during reduction. 83 Figure 10 shows a schematic of the microwave heating system for iron ore reduction in argon, in which two directional couplers were used. By using the couplers ('1' and '2' in Fig.…”
Section: Reduction Of Iron Oxides/ores Laboratory-scale Experimental ...mentioning
confidence: 99%
“…Schematic of microwave iron ore reduction system 83 (reproduced with permission of John Wiley and Sons)…”
Section: Applications Of Microwave Energy To Metallurgymentioning
confidence: 99%
See 1 more Smart Citation
“…A recent work in our group (Sturm et al 2013a) showed that they enable experimentation with a morphologically simple and predictable microwave field and that systems based on these waveguides allow for adaptable process conditions. Moreover, this type of cavity system has already been used in a number of studies for chemical activation with microwave fields (Toukoniitty et al 2009, de Castro et al 2012, Patil et al 2012). …”
Section: Rectangular Waveguide-based Systemsmentioning
confidence: 98%